Leveraging administrative data to better understand and address child maltreatment: a scoping review of data linkage studies - Soneson, E; Das, S; Burn, A-M; van Melle, M; Anderson, JK; Fazel, M; Et al. (SAGE Publications, 2022)
Background This scoping review aimed to overview studies that used administrative data linkage in the context of child maltreatment to improve our understanding of the value that data linkage may confer for policy, practice, and research.